2016
DOI: 10.1007/s40520-016-0587-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion strategy and risk of postoperative delirium in nursing homes residents with hip fracture. A post hoc analysis based on the TRIFE randomized controlled trial

Abstract: In nursing home residents undergoing surgery for hip fracture, maintaining hemoglobin level above 11.3 g/dL reduces the rate of POD on day 10 compared to a RB. Development of POD is associated with increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
3
13
0
1
Order By: Relevance
“…23 surgery, we note no association with amount of units transfused and delirium development, which has been validated by a recent study by Fuchita et al 23 These findings regarding transfusion amount after esophagectomy appear to differ from those in other fields such as orthopedic surgery where liberal transfusion has been noted to be protective against delirium. 29 Our study found no association with duration of procedure consistent with most recently reported data by Fuchita et al 23 ; however, there is no consensus in this observation. 21 Although some have found an association between delirium and gender, 21,27 out study did not find a statistical difference in rates of postoperative delirium between genders.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…23 surgery, we note no association with amount of units transfused and delirium development, which has been validated by a recent study by Fuchita et al 23 These findings regarding transfusion amount after esophagectomy appear to differ from those in other fields such as orthopedic surgery where liberal transfusion has been noted to be protective against delirium. 29 Our study found no association with duration of procedure consistent with most recently reported data by Fuchita et al 23 ; however, there is no consensus in this observation. 21 Although some have found an association between delirium and gender, 21,27 out study did not find a statistical difference in rates of postoperative delirium between genders.…”
Section: Discussionsupporting
confidence: 90%
“…Transfusion has been identified as an independent risk factor for delirium development after multiple types of surgical procedure including esophagectomy . More interestingly in esophageal surgery, we note no association with amount of units transfused and delirium development, which has been validated by a recent study by Fuchita et al These findings regarding transfusion amount after esophagectomy appear to differ from those in other fields such as orthopedic surgery where liberal transfusion has been noted to be protective against delirium . Our study found no association with duration of procedure consistent with most recently reported data by Fuchita et al; however, there is no consensus in this observation .…”
Section: Discussionsupporting
confidence: 88%
“…Blood transfusion, regarded as the quickest and most effective treatment of acute anaemia, is discussed highly controversial in terms of POD. There are indications for both, increasing [32,37] and decreasing [28,38] POD incidences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased risk of postoperative infections including pneumonia, delirium, short-term mortality, length of hospital stay and systemic inflammatory response syndrome in patients receiving blood transfusion(s) was reported [ 4 , 13 17 ]. In contrast, other studies suggest that EBT improves short-term functional outcomes [ 18 – 21 ] and prevents delirium in frail elderly [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 95%